Entrepreneurship and economic growth: Fresh evidence of Iran; Emprendimiento y crecimiento económico: Nueva evidencia de Irán - Majid Aghaei (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
Entrepreneurship is an essential and inexhaustible resource that significantly contributes to the development of countries. It embodies a valuable and cost-effective asset rooted in human creativity and innovation. Societies that prioritize human capital and intellectual capacity over reliance on natural resources tend to achieve greater long-term success. This study investigates the impact of entrepreneurship on economic growth in Iran through the lens of a growth model. Utilizing the Autoregressive Distributed Lags (ARDL) method, the analysis encompasses data from 1980 to 2022. The results indicate that various indices of entrepreneurship exert a positive and significant influence on Iran's economic growth during the specified period. The findings underscore the need for implementing advanced strategies to accelerate growth and align more closely with the Schumpeterian framework. Policymakers are encouraged to emphasize the promotion of innovative entrepreneurial activities to enhance economic growth and development.
Keywords: M13; O40; 330; Entrepreneurship; Economic growth; Autoregressive Distributed Lags (ARDL)